Effects of bradykinin preconditioning in an experimental intestinal ischemia reperfusion model on rats - Dal,Fatih (2020)
Abstract Purpose To investigate the effects of bradykinin on reperfusion injury in an experimental intestinal ischemia reperfusion model. Methods We used 32 Wistar-Albino rats. We composed 4 groups each containing 8 rats. Rats in sham group were sacrified at 100 minutes observation after laparotomy. Thirty minutes reperfusion was performed following 50 minutes ischaemia in control group after observing 20 minutes. Ischaemic preconditioning was performed in one group of the study. We performed the other study group pharmacologic preconditioning by infusional administration of 10 μg/kg/minute bradykinin intravenously. We sacrified all of the rats by taking blood samples to evaluate the lactate and lactate dehydrogenase (LDH) after resection of jejunum for detecting tissue myeloperoxidase (MPO) activity. Results Lactate and LDH levels were significantly higher in control and study groups than the sham group (P<0.001). There is no difference between the study groups statistically. (P>0.05). The results were the same for MPO levels. Although definitive cell damage was determinated in the control group by hystopatological evaluation, the damage in the study groups observed was lower in different levels. However, there was no significant difference between the study groups statistically (P>0.05). Conclusion Either ischeamic preconditioning or pharmacologic preconditioning made by bradykinin reduced the ischemia reperfusion injury at jejunum.